PHYSIOLOGICAL FOUNDATIONS OF THE NERVOUS SYSTEM AND ITS ROLE IN THE REGULATION OF VITAL PROCESSES OF THE HUMAN BODY - Mo’minov M.Sh (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract The nervous system is one of the most important regulatory systems in the human body, coordinating the activity of all organs and physiological systems. This article provides a detailed analysis of the physiological characteristics of the nervous system, the structure and functions of nerve cells, and the mechanisms underlying the generation and transmission of nerve impulses. The functional interrelationship between the central and peripheral nervous systems, the physiological basis of reflex activity, and the influence of the autonomic nervous system on the regulation of internal organ functions are discussed based on scientific evidence. In addition, the clinical significance of nervous system physiology is examined, particularly the role of nervous system dysfunction in the development of various neurological and psychosomatic disorders. The article also highlights the positive effects of a healthy lifestyle, stress management, adequate sleep, and physical activity on nervous system function, with preventive aspects substantiated from a medical perspective.